H. Putnam: Criteria of Rationality Within the Context of Internal Realism - Vasiliauskaitė, Giedrė (Problemos, 2001)
The concept of Rationality is said to be in crisis in the philosophy of the second part of twentieth century. One of the great contemporary American thinkers Hilary Putnam tries to rehabilitate this notion and to design the approach that would be appropriate to his internal realism. Putnam presents several arguments to criticize and refute unacceptable standpoint of metaphysical realism. It is based on the correspondence theory of truth and on the assumptions that the world has the structure independent of human consciousness and conceptualization and that there exists only one full and correct description of the world. In the case of internal realism, situation is quite the opposite: there is the plurality of such descriptions, and the world’s way to be is shaped by taking into account interests, values and attitudes. The truth is said by Putnam to be the limit notion of rational acceptability under epistemically ideal conditions. Particular criteria of rationality are permanently approaching this limit by participating in the dialogue with each other. The crucial innovative idea of Putnam’s conception is the thesis that the concept of rationality is essentially rooted in the interdependence of fact and value. Ls this interdependence tenable? Can it persist in the epistemically ideal conditions? How particular criteria of rationality can cope with the challenges of relativism? The main task of this paper is to show that the reconsidered conception of rationality must involve values and social aspects and abandon the claim to universality.